Linguistic and content validation of the stroke impact scale (SIS) 3.0 in three languages - Ahmad Ainuddin, Husna; Romli, Muhammad Hibatullah; SF Salim, Mazatulfazura; Hamid, Tengku Aizan; Mackenzie, Lynette (Universiti Putra Malaysia, 2023)
Introduction: A stroke can have devastating consequences and may reduce the Quality of Life (QoL) of stroke survivors. Specific QoL measurement is therefore needed to appreciate and quantify the impact of this condition. The objective of the study is to culturally adapt, translate and validate the Bahasa Melayu, Mandarin and Tamil versions of the Stroke Impact Scale (SIS) 3.0 for its application in clinical practice and stroke research in Malaysia. Methods: A total of nine translators translated the SIS 3.0 and five professional experts carried out the linguistic validation of the SIS 3.0 in accordance with the Mapi Research Institute’s linguistic validation guideline. The steps for linguistic validation included forward translation, synthesis, backward translation, clinicians’ review, and cognitive debriefing. Ten to thirteen healthcare practitioners rated the translated versions of SIS 3.0 using the Content Validity Index (CVI) and Content Validity Ratio (CVR). Results: During the translation processes, concerns were expressed about various grammatical and semantic issues, such as the appropriateness of some phrases used for the Malaysian demographic. The Scale-CVI average was 0.91 and 0.95 for relevance and clarity respectively which indicated excellent content validity. The CVR values ranged from 0.40 to 1.00. Conclusion: The Bahasa Melayu, Mandarin and Tamil versions of SIS 3.0 was well developed. The translated versions of SIS 3.0 could be adopted in clinical, community and educational settings. Nevertheless, further in-depth psychometric testing including construct validity and reliability on a larger sample among the multi-ethic Malaysians stroke survivors is advised.